2011
DOI: 10.1590/s0004-282x2011000500007
|View full text |Cite
|
Sign up to set email alerts
|

Pressure pain threshold in the craniocervical muscles of women with episodic and chronic migraine: a controlled study

Abstract: Objective: To estimate the pressure pain threshold (PPT) of the craniocervical muscles in women with episodic migraine (EM) n=15 and chronic migraine (CM) n=14, and in healthy volunteers (C) n=15. Method: A blinded examiner obtained the PPT bilaterally, by pressure algometry, for the following muscles: frontalis, temporalis, masseter, trapezius and sternocleidomastoid. ANOVA (p<0.05) was used for statistical purposes. Results: Contrasted to controls, individuals with EM had significantly decreased PPT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 29 publications
6
49
1
4
Order By: Relevance
“…Our findings are in agreement with a study that evaluated women with episodic and chronic migraine [30]. In our study, the painful thresholds in migraine and TTH patients were lower than the control group at all points stimulated, similar to other studies with primary headaches, as seen in Table 4.…”
Section: /6supporting
confidence: 93%
“…Our findings are in agreement with a study that evaluated women with episodic and chronic migraine [30]. In our study, the painful thresholds in migraine and TTH patients were lower than the control group at all points stimulated, similar to other studies with primary headaches, as seen in Table 4.…”
Section: /6supporting
confidence: 93%
“…They observed excellent inter-(ICC 0.97) and intra-rater (ICC 0.98) reliability. Other authors also showed a good reliability for this technique in other parts of the body; the first dorsal interosseous muscle [1], the neck and head muscles [4,6,7,17,24] or following a spinal manipulation [25].…”
Section: Discussionmentioning
confidence: 84%
“…Volunteers remained seated in a chair, with the torso upright, leaning back, feet flat on the floor and hands resting on the legs. For the evaluation of the deltoid muscle, gradual pressure was applied at the midpoint between its origin and insertion, and for the descending part of the trapezius, constant gradual pressure was applied at half the distance between the spinous process of the 7th cervical vertebra and the acromion of the scapular (21) . The evaluator exercised gradual compression perpendicular to the muscle fibers until the volunteer reported any intensity of pain, at which point this value was recorded.…”
Section: Pressure Pain Thresholdmentioning
confidence: 99%